Obtenção de suplemento alimentar na forma de comprimidos orais dispersíveis (ODT'S) contendo berberina nanoencapsulada - Souza, Luma Borges de (2020)
Berberine is a natural compound that has been used by the food and pharmaceutical industry as a dye or because of its bioactivity. However, berberine has limited water solubility, which makes it difficult to use it on a larger scale in the formulation of foods or dietary supplements. It is known that low solubility also decreases its absorption by the body and its bioavailability and encapsulation techniques can be an alternative to overcome this situation. A promising way of providing bioactive compounds to consumers is the formulation of orodispersible tablets (ODTs). The present study aimed to obtain orodispersible tablets containing nanoencapsulated berberine. The characterization of the morphological and physical-chemical properties of the nanoparticles was carried out, as well as the characterization of the color and texture of the tablets. UV-Vis tests showed that the mass ratio of Poloxamer: berberine of 8:1 (wt:wt) led to the formation of nanoparticles, although a 10: 1 mass ratio was adopted as a safety criterion. The differential scanning calorimetry, infrared spectroscopy and X-ray diffraction analyzes demonstrated the encapsulation of berberine in the Poloxamer polymer matrix. The tablets were obtained at concentrations 0 % (without addition of berberine), 1, 3, 10 and 20% (by weight), showing that concentrations above 10% caused changes in the mechanical properties and the color of the tablets. Also, these parameters suggested the concentration of 3% as promising for obtaining orodispersible tablets.